ETHICAL JUDGMENT AND DECISION-MAKING AMONG TAX VOLUNTEERS: A CASE STUDY OF THE UNIVERSITY INDONESIA TAX ADMINISTRATION’S VOCATIONAL EDUCATION PROGRAM - Elsie Sylviana Kasim; Yulial Hikmah (Jurnal Administrasi Bisnis Terapan, 2020)
This study aims to determine whether tax volunteers in the Tax Administration Department of the University of Indonesia’s Vocational Education Program are engaged in the development of ethical judgment and decision-making. The data collection technique used in this study is field study (field research) wherein survey questionnaires were administered before and after the implementation of the tax volunteer program. The results of research and analysis concluded that participation among tax volunteers can improve students’ ethical judgment and their ability to make ethical decisions in income scenarios but not in deduction scenarios.Keyword : ethical assessment, ethical decision-making, tax volunteers